Formulasi Dan Evaluasi Sediaan Shampoo Dengan Bahan Dasar Ekstrak Bunga Chamomile (Matricaria Chamomilla) : Literature Review Article - Nia Yuniarsih; Audia Nazwa Zanuba Adam; Jihan Khairunnisa; Meika Hestina Putri; Nabilla Atqia Shakira; Putri Septiyani; Winda Aryani (Peneliti.net, 2023)
Hair is the outermost part of the body so it cannot be separated from the bad effects of exposure to sunlight, pollution, cosmetic ingredients and other cleaning agents. Free radicals can come from pollution, dust, or are produced continuously as a consequence of metabolism. To protect itself from free radicals, the body produces anti-free radical compounds called antioxidants. Chamomile (Matricia chamomilla) which contains apigenin as an active substance is known as a hair-lightening agent and can be used as an antioxidant. The application of this flower is inconvenient, so incorporating its extract into a shampoo to clean the scalp and hair gives better results.